2003
DOI: 10.1007/s00442-002-1154-7
|View full text |Cite
|
Sign up to set email alerts
|

The carbon charging of pines at the climatic treeline: a global comparison

Abstract: The carbon charging of pines across the treeline ecotone of three different climatic zones (Mexico 19 degrees N Pinus hartwegii, Swiss Alps 46 degrees N P. cembra and northern Sweden 68 degrees N P. sylvestris) was analyzed, to test whether a low-temperature-driven carbon shortage can explain high-elevation tree limits, and whether the length of the growing season affects the trees' carbon balance. We quantified the concentrations of non-structural carbohydrates (NSC) and lipids (acylglycerols) in all tree org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
246
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 284 publications
(271 citation statements)
references
References 45 publications
(44 reference statements)
15
246
5
Order By: Relevance
“…This might be due to the stronger synthesis of fat for their stronger frost resistances in the higher altitudes. Similar findings were also observed for pine needles, tree bark and xylem tissues (Hoch and Korner, 2003;Yang et al, 2013). To avoid the influence of altitudes on the concentration and lipid (or TOC) content, partial correlation analysis was carried out and indicated that there was no significant correlation between the soil TOC and the concentrations of each targeted compound, which was different from the observation of Yang's work where most of OCPs were significantly linearly correlated with the soil TOC (Yang et al, 2013).…”
Section: Concentrations and Profiles Of Svocs In Lichen Moss And Soisupporting
confidence: 55%
See 1 more Smart Citation
“…This might be due to the stronger synthesis of fat for their stronger frost resistances in the higher altitudes. Similar findings were also observed for pine needles, tree bark and xylem tissues (Hoch and Korner, 2003;Yang et al, 2013). To avoid the influence of altitudes on the concentration and lipid (or TOC) content, partial correlation analysis was carried out and indicated that there was no significant correlation between the soil TOC and the concentrations of each targeted compound, which was different from the observation of Yang's work where most of OCPs were significantly linearly correlated with the soil TOC (Yang et al, 2013).…”
Section: Concentrations and Profiles Of Svocs In Lichen Moss And Soisupporting
confidence: 55%
“…Lichen is a complex life form that lives symbiotically with fungi and algae; thus, the decreasing temperature with increasing altitude might be related to the altitude-dependent gradient trend of SVOCs in lichens. Additionally, the host trees at the higher altitudes might ooze more hydrophobic oils to resist frost than those at lower altitudes, which may increase the lipid contents of lichens, further improving the uptake capacity of SVOCs for lichens in the higher altitude regions (Hoch and Korner, 2003;Yang et al, 2013). Conversely, a range of other studies also noted similar altitude-dependent gradient trend/cold-trapping effects for HCHs (Blais et al, 1998;Blais et al, 2003;Davidson et al, 2003;Shen et al, 2004), DDTs Davidson et al, 2003;Shen et al, 2005), endosulfan II and PCBs (Blais et al, 1998) in the Canadian Rocky Mountains and the Alps.…”
Section: Key Factors Governing the Distributions Of Svocs On The Soutmentioning
confidence: 91%
“…On the other hand, nonstructural carbon reserves (e.g. Sveinbjörnsson et al 1992, Skre 1993, Grace et al 2002, Hoch & Körner 2003, Shi et al 2006) may compensate for the effects of low soil temperature during the early growing season. In dry climates and during dry summers, moisture supply from melting snow drifts may mitigate moisture stress in late spring and early summer.…”
Section: Influence Of Tree Groups On Wind and Resultant Effectsmentioning
confidence: 99%
“…build new structures (< 5 °C; Körner 2003). As a consequence of limits to tissue growth, plants accumulate non-structural carbohydrates and even lipids (Hoch and Körner 2003). For leaf starch formation this observation dates back to the mid-nineteenth century (Krause 1869).…”
Section: Introductionmentioning
confidence: 99%